A Model for Recruiting Clinical Research Participants With Anxiety Disorders in the Absence of Service Provision: Visions, Challenges, and Norms Within a Canadian Context. Issue 12 (December 2015) - Moscovitch, David A.; Shaughnessy, Krystelle; Waechter, Stephanie; Xu, Mengran; Collaton, Joanna; Nelson, Andrea L.; Barber, Kevin C.; Taylor, Jasmine; Chiang, Brenda; Purdon, Christine
Abstract : Abstract: High-quality research in clinical psychology often depends on recruiting adequate samples of clinical participants with formally diagnosed difficulties. This challenge is readily met within the context of a large treatment center, but many clinical researchers work in academic settings that do not feature a medical school, hospital connections, or an in-house clinic. This article describes the model we developed at the University of Waterloo Centre for Mental Health Research for identifying and recruiting large samples of people from local communities with diagnosable mental health problems who are willing to participate in research but for whom treatment services are not offered. We compare the diagnostic composition, symptom profile, and demographic characteristics of our participants with treatment-seeking samples recruited from large Canadian and American treatment centers. We conclude that the Anxiety Studies Division model represents a viable and valuable method for recruiting clinical participants from the community for psychopathology research.